2016
DOI: 10.1093/ije/dyw310
|View full text |Cite
|
Sign up to set email alerts
|

Does job promotion affect men’s and women’s health differently? Dynamic panel models with fixed effects

Abstract: The present study indicates that a job promotion could lead to decreased SRH and increased symptoms of depression in a 2-4-year perspective. Associations appear to differ for women and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…On the one hand, the large majority of the existing evidence is from single-country cross-sectional analyses that did not find any interactive association between gender and SES with health at older ages (Damian et al , 1999; Knurowski et al , 2004; Sulander et al , 2009; Connolly, O’Reilly, and Rosato, 2010). The same results were found in studies based on national longitudinal studies from England (Melzer et al , 2000; McMunn, Nazroo, and Breeze, 2008), Spain (Orfila et al , 2006), and Sweden (Parker et al , 2013). On the other hand, the association between SES and health was found to be stronger in older men than in older women in one study from Spain (Regidor et al , 1999).…”
Section: Gender Inequalities In Health: Possible Underlying Mechanismssupporting
confidence: 82%
“…On the one hand, the large majority of the existing evidence is from single-country cross-sectional analyses that did not find any interactive association between gender and SES with health at older ages (Damian et al , 1999; Knurowski et al , 2004; Sulander et al , 2009; Connolly, O’Reilly, and Rosato, 2010). The same results were found in studies based on national longitudinal studies from England (Melzer et al , 2000; McMunn, Nazroo, and Breeze, 2008), Spain (Orfila et al , 2006), and Sweden (Parker et al , 2013). On the other hand, the association between SES and health was found to be stronger in older men than in older women in one study from Spain (Regidor et al , 1999).…”
Section: Gender Inequalities In Health: Possible Underlying Mechanismssupporting
confidence: 82%
“… 18 Job promotion also appeared to increase depressive symptoms and a decrease self-rated general health, at least in a short-term perspective. 19 …”
Section: What Has Been Found? Key Findings and Publicationsmentioning
confidence: 99%
“…Some studies have shown that working women have more stress-related disorders than housewives. 19 , 20 Therefore, we believe that our participants might have been less exposed to stres, affecting their QoL results.…”
Section: Discussionmentioning
confidence: 98%